x+(x+1)+(x+2)+(x+3)+(x+4)=38

Simple and best practice solution for x+(x+1)+(x+2)+(x+3)+(x+4)=38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x+1)+(x+2)+(x+3)+(x+4)=38 equation:


Simplifying
x + (x + 1) + (x + 2) + (x + 3) + (x + 4) = 38

Reorder the terms:
x + (1 + x) + (x + 2) + (x + 3) + (x + 4) = 38

Remove parenthesis around (1 + x)
x + 1 + x + (x + 2) + (x + 3) + (x + 4) = 38

Reorder the terms:
x + 1 + x + (2 + x) + (x + 3) + (x + 4) = 38

Remove parenthesis around (2 + x)
x + 1 + x + 2 + x + (x + 3) + (x + 4) = 38

Reorder the terms:
x + 1 + x + 2 + x + (3 + x) + (x + 4) = 38

Remove parenthesis around (3 + x)
x + 1 + x + 2 + x + 3 + x + (x + 4) = 38

Reorder the terms:
x + 1 + x + 2 + x + 3 + x + (4 + x) = 38

Remove parenthesis around (4 + x)
x + 1 + x + 2 + x + 3 + x + 4 + x = 38

Reorder the terms:
1 + 2 + 3 + 4 + x + x + x + x + x = 38

Combine like terms: 1 + 2 = 3
3 + 3 + 4 + x + x + x + x + x = 38

Combine like terms: 3 + 3 = 6
6 + 4 + x + x + x + x + x = 38

Combine like terms: 6 + 4 = 10
10 + x + x + x + x + x = 38

Combine like terms: x + x = 2x
10 + 2x + x + x + x = 38

Combine like terms: 2x + x = 3x
10 + 3x + x + x = 38

Combine like terms: 3x + x = 4x
10 + 4x + x = 38

Combine like terms: 4x + x = 5x
10 + 5x = 38

Solving
10 + 5x = 38

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 5x = 38 + -10

Combine like terms: 10 + -10 = 0
0 + 5x = 38 + -10
5x = 38 + -10

Combine like terms: 38 + -10 = 28
5x = 28

Divide each side by '5'.
x = 5.6

Simplifying
x = 5.6

See similar equations:

| -x+8=87 | | 4x-3y-17=0 | | -2x-6=21 | | 6.7+0.356+4= | | X^4+8x^2-52=0 | | (b+4)(b-3)(2b-1)=0 | | 32t-5t^3=0 | | x-(7/8)=(x-6)/12 | | 5t-3t^2=0 | | (z-1)(4z+2)=0 | | 63=7v+2v | | 7=8x-x | | (2-1)(4z+2)=0 | | 29x-5y=3 | | y=y^4-26y^2+164 | | (y-4)(3x+5y-2)=0 | | (3y-8)(-x+y)=0 | | (-2x^2-4y)(3x+4)=0 | | 4(1)y-3+3=0 | | 4((1-3y)/2) | | 4xy+3x-3=0 | | 7[5-(4x-3)]+3x=0 | | 3z/10-2=3 | | 4y-(y*y)=-1000 | | 2/?=18/45 | | 4y-y*y=-1000 | | 4-3x+2x= | | 0,2(x-4)=0,4(x-3) | | logx(8x-15)=2 | | 24x-13=15x+5 | | 21x+6-2x+20=70 | | 3x^6-18=0 |

Equations solver categories